2012
DOI: 10.1179/2045772312y.0000000045
|View full text |Cite
|
Sign up to set email alerts
|

Using scoping review methods to describe current capacity and prescribe change in Canadian SCI rehabilitation service delivery

Abstract: Objective: To describe the methodology used to conduct a scoping review of spinal cord injury (SCI) rehabilitation service delivery in Canada, and to explain the reporting process intended to advance future service delivery. Evidence acquisition: A SCI rehabilitation framework derived from the International Classification of Function, Disability and Health was developed to describe the goals and interprofessional processes of rehabilitation. An adapted Arksey and O'Malley (2005) methodological framework was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 6 publications
0
43
0
Order By: Relevance
“…In Canada, progress in this area includes recent investments by the Canadian Federal and Provincial branches of Government to the Rick Hansen Institute's "Care Program" 81 that has funded a number of research and knowledge translation activities with clear linkages at the research, clinical, and policy levels. [82][83][84][85] These resources elevates the SCI research field's ability to easily access information and/or tools to better address pain, which may be of use to help inform the wide range of information needs of people with SCI and their family members and caregivers. In general, there has been a clear gain in the number of research studies in the area of pain, but the ability to generalize findings into clinical practice remains problematic.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, progress in this area includes recent investments by the Canadian Federal and Provincial branches of Government to the Rick Hansen Institute's "Care Program" 81 that has funded a number of research and knowledge translation activities with clear linkages at the research, clinical, and policy levels. [82][83][84][85] These resources elevates the SCI research field's ability to easily access information and/or tools to better address pain, which may be of use to help inform the wide range of information needs of people with SCI and their family members and caregivers. In general, there has been a clear gain in the number of research studies in the area of pain, but the ability to generalize findings into clinical practice remains problematic.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of Cardiometabolic Health as a Domain of interest for developing indicators emerged from the environmental scan (E-Scan) consensus-building activity designed to select the broader set of Domains. 26 This process involved a systematic search to collect information about SCI/D rehabilitation care related to Cardiometabolic Health and factors that influence the outcome of rehabilitation interventions and a scoping synthesis of the acquired data. Medline and Embase databases were searched using the terms "cardiometabolic health", "spinal cord injury", or both.…”
Section: Driver Diagram and Construct Definitionmentioning
confidence: 99%
“…The atlas represents an amalgamation of a national data set describing current rehabilitation resources and service delivery, results of a scoping review, and the expert opinion of 46 coauthors, and 86 collaborators from 15 tertiary SCI rehabilitation centres across the nation regarding the current state of SCI rehabilitation knowledge generation, clinical application, and policy change in Canada. An overall framework for understanding the rehabilitation process is presented in the atlas [13]; summary data from the scoping review is presented throughout the atlas as it relates to specific goals of rehabilitation (i.e., maintaining skin integrity or developing independence in breathing). Intended for use by multiple stakeholders (clinicians, administrators, non-governmental organizations, etc.…”
Section: Spinal Cord Injurymentioning
confidence: 99%
“…), the atlas attempts to: facilitate program self-evaluation and service enhancements; articulate future research and health policy agendas; and inform accreditation processes and best practice implementation. Through the scoping review methodology employed by the authors [13], the atlas identified national trends, gaps (regional and/or process disparity) and priorities in SCI rehabilitation service delivery. This article presents key national perspectives derived from the scoping review process that warrant international reflection and dialogue.…”
Section: Spinal Cord Injurymentioning
confidence: 99%